PEMBUATAN NUGGET IKAN KEMBUNG DENGAN PENAMBAHAN BAYAM MERAH - kartika, Nilda; Efendi, Raswen; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The purpose of this study was to obtain the best ratio of mackerel and red spinach in making nugget. The research method used a completely randomized design with five treatments and three replications. The treatments in the study consisted of IB1 = mackerel : red spinach (90:10), IB2 = mackerel : red spinach (85:15), IB3 = mackerel : red spinach (80:20), IB4 = mackerel : red spinach (75:25), IB5 = mackerel : red spinach (70:30). The data obtained were analyzed statistically using analysis of variance and continued with the Duncan’s New Multiple Range Test (DNMRT) at the 5% level. The results showed that the ratio of mackerel and red spinach meat significantly affected moisture content, ash content, fat content, protein content, fiber content, descriptive and hedonic sensory assessment on the attributes of color, aroma, chewiness, taste, and overall assessment. Based on this research, the best treatment is IB2 = mackerel : red spinach (85:15) with a moisture content of 45.04%, an ash content of 0.76%, a fat content of 4.31%, a protein content of 12.43%, a crude fiber content 0.31%, and antioxidants 1.506.13 ppm. Based on sensory observations the panelists generally preferred hedonic with a description of a grayish brown color, fish scented, slightly chewy, slightly fishy taste and slightly spinach taste.Keywords: nugget, mackerel, red spinach.